2020
DOI: 10.1080/09612025.2020.1807690
|View full text |Cite
|
Sign up to set email alerts
|

Parenting during the Covid-19 pandemic of 2020: academia, labour and care work

Abstract: The Covid-19 pandemic instigated fundamental challenges and changes to parents' working lives in Britain. This viewpoint article reflects upon the experience of balancing childrearing responsibilities with academic work across the Spring and Summer of 2020. It positions the removal of formal and informal childcare networks within the history of feminist demands around childcare and sets it against the background of the recent history of women and reproduction within Higher Education in Britain. Drawing upon fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 11 publications
1
45
0
5
Order By: Relevance
“…Responses to the pandemic including lockdowns, cancelled services, and other public health measures have magnified many of these stressors. Emerging research has identified the emotional and practical demands of working at home (and at times longer than usual hours), childrearing for 24 hours a day, 7 days a week, restriction of access to public spaces, and balancing the demands of paid employment with the increased responsibilities from having children at home [3] . Studies from countries such as Singapore show that the extreme financial and health insecurity, along with physical and social isolation because of COVID-19, can increase tensions in the home environment [4] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Responses to the pandemic including lockdowns, cancelled services, and other public health measures have magnified many of these stressors. Emerging research has identified the emotional and practical demands of working at home (and at times longer than usual hours), childrearing for 24 hours a day, 7 days a week, restriction of access to public spaces, and balancing the demands of paid employment with the increased responsibilities from having children at home [3] . Studies from countries such as Singapore show that the extreme financial and health insecurity, along with physical and social isolation because of COVID-19, can increase tensions in the home environment [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence also reveals the gendered effects of challenges and stressors associated with the pandemic, which are disproportionately experienced by mothers [5] , [6] . During the first month of the lockdown, for example, women in the United Kingdom spent on average two-thirds more time on childcare responsibilities than men; in addition, mothers were interrupted much more often than fathers, greatly affecting their ability to work from home during the pandemic [3] . The requirement to stay at home affected mothers' independence, skill acquisition, and feeling of purpose often associated with paid employment outside the home, resulting in isolation, suffocation, boredom, and feelings of oppression and imprisonment [3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although working from home may have slowed down research publications and progress, in many cases it simply added more backstage "things to do" to a busy academic life as children were kept at home for many months and expected to maintain some kind of learning timetable (Crook, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Zatvorenost odgojno-obrazovnih institucija odrazila se i na obrazovanje djece. Potreba održavanja kontinuiteta obrazovanja moguće je potaknula i veću angažiranost roditelja (Crook, 2020) što potvrđuju i nalazi ovog istraživanja. Roditelji su usmjereni na aktivnosti i igre za spoznajni razvoj djece te bazične aktivnosti, dok se zapostavlja kreativnost.…”
Section: Raspravaunclassified